2013
DOI: 10.1089/ten.tea.2012.0357
|View full text |Cite
|
Sign up to set email alerts
|

A Platelet-Rich Plasma-Based Membrane as a Periosteal Substitute with Enhanced Osteogenic and Angiogenic Properties: A New Concept for Bone Repair

Abstract: The periosteum plays a pivotal role during bone development and repair contributing to bone vascularization and osteoprogenitor cells source. We propose a periosteal substitute engineered using a platelet-rich plasma (PRP) membrane incorporating autologous bone marrow-derived mesenchymal stem cells (PRP/BMSC gel membrane) to be wrapped around an osteoconductive scaffold for regeneration of compromised bone defects. The PRP/BMSC gel membrane was optimized using different compositions for optimal release of vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 38 publications
1
55
0
1
Order By: Relevance
“…Mouse: [223] (hVEGF/hMPC), [224] (hVEGF/hBMP2/hMPC) Rat: [225] (hBMP2/hMPC), [226] (hBMP7/hMPC) Rabbit: [227], [228] (PRP/rbMPC),…”
Section: Mpcs With Growth Factors/compoundsmentioning
confidence: 99%
“…Mouse: [223] (hVEGF/hMPC), [224] (hVEGF/hBMP2/hMPC) Rat: [225] (hBMP2/hMPC), [226] (hBMP7/hMPC) Rabbit: [227], [228] (PRP/rbMPC),…”
Section: Mpcs With Growth Factors/compoundsmentioning
confidence: 99%
“…A number of studies have investigated combination treatment with PDGF and several other growth factors including bFGF (Meraw et al, 2000), BMP-2 (Martino et al, 2011), BMP-7 (Zhang et al, 2009b, IGF-1 (Nociti Junior et al, 2000), osteogenin (Marden et al, 1993), TGF-Ī²1 and VEGF (El Backly et al, 2013). Bone formation was reported to increase between 1.4 and 2.3 fold (Zhang et al, 2009b) within large animals (dog (Zhang et al, 2009b)) following PDGF dosages around 5 Āµg/mL for direct administration (Nociti Junior et al, 2000), or 2 x 10 10 / mL viral particles for indirect administration (Zhang et al, 2009b).…”
Section: Combination Administration Of Pdgfmentioning
confidence: 99%
“…Bone formation was reported to increase between 1.4 and 2.3 fold (Zhang et al, 2009b) within large animals (dog (Zhang et al, 2009b)) following PDGF dosages around 5 Āµg/mL for direct administration (Nociti Junior et al, 2000), or 2 x 10 10 / mL viral particles for indirect administration (Zhang et al, 2009b). Combination treatments within small animal (mouse (El Backly et al, 2013), rabbit and rat (Park et al, 2013)) studies reported increased bone formation between 2.5 (Xu D Gothard et al Tissue engineered bone and clinical translation et al, 2012) and 10 fold following PDGF dosages ranging between 0.05 (Martino et al, 2011) and 200 Āµg (Marden et al, 1993).…”
Section: Combination Administration Of Pdgfmentioning
confidence: 99%
“…These scaffolds have been shown to support orthotopic bone formation in a rabbit model [2]. Immediately before surgery, 2.5 Ā· 10 6 UC-MSCs were loaded onto the scaffolds and embedded in a fibrin glue (Tissucol; Baxter).…”
Section: Assessment Of Bone Formation In the Mouse Calvarial Defectmentioning
confidence: 99%
“…The implantation of these cells combined with ceramic-based biomaterials in bone defects gives the best results in terms of bone formation both in animal models [2,3] and in patients [4]. Although BM-MSCs are a feasible and autologous source of MSCs, their painful and invasive collection method has limited their use.…”
mentioning
confidence: 99%